Investigating the Role of Protein Arginine Methyltransferases in Breast Cancer Etiology - Morettin, Alan James (Université d'Ottawa / University of Ottawa, 2015)
Breast cancer is the most commonly diagnosed cancer amongst Canadian women. Though numerous treatments are available, in many instances tumours become refractory or recur. Therefore, understanding the biological events that lead to the progression and therapeutic resistance of breast cancer is essential for the development of novel treatment options for this disease. Numerous members of the protein arginine methyltransferase (PRMT) family, which are the enzymes responsible for catalyzing methylation on arginine residues are aberrantly regulated in breast cancer. Hence, understanding the precise contribution of PRMTs to the development and progression of breast cancer is important. This Thesis will present my findings on the alternatively spliced PRMT1 isoform, PRMT1v2, previously identified to be overexpressed in breast cancer cell lines and here shown to promote breast cancer cell survival and invasion. Second, a novel role is ascribed to PRMT6, another PRMT aberrantly expressed in breast cancer. PRMT6 promotes chemoresistance to the drug bortezomib by mediating stress granule formation through down-regulation of eIF4E. Increased stress granule formation in bortezomib-resistant cancer cells promotes cell survival. Third, DDX3, a prototypical PRMT substrate which is overexpressed in breast cancer cell lines and stimulates transformation of mammary epithelial cells is a novel substrate of PRMT1, CARM1, and PRMT6. Lastly, TDRD3, a reader/effector of arginine methylation also overexpressed in breast tumours regulates breast cancer cell proliferation, anchorage-independent growth and cell motility and invasion.
Keywords: Arginine Methylation; PRMTs; Breast Cancer